Dual mechanisms regulate ecosystem stability under decade-long warming and hay harvest - Zheng Shi (Nature Portfolio, 2016)
Species diversity is thought to play an important role in maintaining production stability. Shi et al.demonstrate that the dominant C4 plant also makes a substantial contribution to temporal stability in a grassland ecosystem subject to 15 years of experimental warming and hay harvest.